Balthasar Neumann und seine Krankheit - Sauerbruch, Tilman; Satzinger, Georg (DMW - Deutsche Medizinische Wochenschrift, 2019)
On August 26 in 1753, Balthasar Neumann’s wife wrote a letter to the Abbot of Neresheim describing her husband’s disease one week after his death. This article outlines Neumann’s medical history and builds connections towards the understanding of diseases in these times. As an example – and probably Neumann’s ailment – the gastric cerarcinoma is discussed with special attention in this report.
Keywords: Balthasar Neumann; Krankheit; Todesursache; Krankheitsverständnis; 18. Jahrhundert